ICT usage increases workforce geographical diversity - Pengjun Zhao; Hao Wang; William A. V. Clark; Yongheng Feng; Qiyang Liu; Yanzhe Cui (Proceedings of the National Academy of Sciences, 2025)
The adoption of information and communication technology (ICT) by rural–urban migrants is reshaping job-search mobility, significantly shaping city-level workforce geographical diversity. This study provides compelling evidence of ICT’s impact by examining China’s cities. We introduce the rural–urban migrant workforce Geographical Diversity Index (GDI), a metric that captures the mobility patterns of 20 million migrant workers across Chinese cities from Q1 2019 to Q4 2023. This study highlights how ICT usage shapes migration dynamics and connectivity across geographic spaces, with implications for labor mobility and urban inclusivity. Using panel vector autoregression models, we establish a causal relationship between ICT usage and GDI, revealing heterogeneous impacts: large cities and male workers benefit more from ICT usage than small cities and female workers. While ICT-driven diversity enhances labor productivity, it also increases migrant workers’ job-hunting travel distances, contributing to higher carbon emissions. These findings underscore the dual role of ICT as a facilitator of inclusivity and a source of sustainability challenges, offering critical insights for policymakers aiming to leverage digital tools for equitable and sustainable urban development.